Linzizong Volcanic Rocks in Linzhou of Tibet: A Volcanic Petrologic Assemblage in Continental Collision Environment - Dong, Guochen; Mo, Xuanxue; Zhao, Zhidan; Wang, Liang; Zhao, Su (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 128